Reverse-Penetrating Head Injury Caused by Falling on Sharp-Edged Stone: A Case Report - Bhat, Abdul Rashid; Raswan, Uday Singh; Kirmani, Altaf R.; Choudhary, Neeraj Kumar; Sarmast, Arif (Indian Journal of Neurotrauma, 2015)
Penetrating injury is usually caused by a traumatizing object when it moves from its place of rest—that is, fired from a weapon, falls from the height, hurled from hand, or flown by wind—to reach and penetrate the static subject. These injuries are potentially life threatening, which can occur in military as well as in civilian societies. However, a case of reverse-penetrating cranial injury was encountered, when a 4-year-old male child fell from height, hitting his head against sharp-edged stones on the ground. The parts of the stones were retained in the epidural space after fracturing the cranial vault and were undetected by CT scan head. Thus, reversely, the subject moved toward the static object and caused injury. The medicolegal implications of such a trauma are high in a geographical region where mobs and police resort to stone pelting.
Keywords: reverse-penetrating head injury; undetected stone; medicolegal implications